2015
DOI: 10.1038/sj.bdj.2015.250
|View full text |Cite
|
Sign up to set email alerts
|

Survival characteristics of 771 resin-retained bridges provided at a UK dental teaching hospital

Abstract: The five-year and ten-year survival rates estimated by the life-table method are 80.8% (95% confidence interval 78.0-83.6%) and 80.4% (95% confidence interval 77.6-83.2%) respectively. The median survival cannot be estimated for this study as the survival probability remains above 80% even at the longest follow-up. Analysis of clinical variables influencing survival revealed that design of the restoration and experience of the operator providing the restoration were significant factors. Resin-retained bridges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 13 publications
0
47
0
3
Order By: Relevance
“…It has often been considered that they are an under-utilised restoration modality in general dental practice due to a perceived high rate of clinical failure, which may be associated with incorrect design and execution 3 . A recent prospective study of 771 adhesive bridges by King et al (2015) found that most failures of RBBs occurred within the first four years, and that very few failed thereafter, with an estimated survival rate of 80.4% at 10 years 4 . In this singlecentre study, because the point of failure was recorded as the first de-bond, the overall survival in clinical service may have been greater where bridges had been re-bonded successfully.…”
Section: How Long Can Rbbs Last?mentioning
confidence: 99%
See 1 more Smart Citation
“…It has often been considered that they are an under-utilised restoration modality in general dental practice due to a perceived high rate of clinical failure, which may be associated with incorrect design and execution 3 . A recent prospective study of 771 adhesive bridges by King et al (2015) found that most failures of RBBs occurred within the first four years, and that very few failed thereafter, with an estimated survival rate of 80.4% at 10 years 4 . In this singlecentre study, because the point of failure was recorded as the first de-bond, the overall survival in clinical service may have been greater where bridges had been re-bonded successfully.…”
Section: How Long Can Rbbs Last?mentioning
confidence: 99%
“…In this singlecentre study, because the point of failure was recorded as the first de-bond, the overall survival in clinical service may have been greater where bridges had been re-bonded successfully. An evidence-informed summary of key papers assessing RBBs has been given in Table 1 4,5,6,7,8,9 . Careful case selection, appropriate design and attention to operative detail are key factors for the clinical longevity of RBBs and will therefore be covered in this paper.…”
Section: How Long Can Rbbs Last?mentioning
confidence: 99%
“…Cantilever resin‐bonded bridges demonstrate better survival than fixed‐fixed resin‐bonded bridges with 5‐year survival of 86.3% and 71.9%, respectively (King et al . ). The most common mode of failure for resin‐bonded bridges is debonding (Pjetursson et al .…”
Section: Extractionmentioning
confidence: 97%
“…When the enamel of the abutment tooth has been preserved during preparation and adequate occlusal coverage has been provided, resin-bonded bridges have been shown to have a median survival of 9.8 years (Djemal et al 1999). Cantilever resin-bonded bridges demonstrate better survival than fixed-fixed resinbonded bridges with 5-year survival of 86.3% and 71.9%, respectively (King et al 2015). The most common mode of failure for resin-bonded bridges is debonding (Pjetursson et al 2007); this can usually be managed conservatively and without compromise to the abutment tooth.…”
Section: Resin-bonded Bridgesmentioning
confidence: 99%
“…A recent study by King et al showed that tooth preparation was a negative predictor for success of laboratory made resin bonded bridges. 19 The restorative status of the abutment(s) will also affect prognosis. Restorations can be a negative predictor of prognosis but sometimes the cavities can be used to aid with mechanical retention.…”
Section: Prognosismentioning
confidence: 99%